Evaluation of four sampling devices for Burkholderia pseudomallei laboratory aerosol studies. - Michael Schuit; Sierra Gardner; Jill Taylor; Paul Dabisch (Public Library of Science (PLoS), 2021)
Previous field and laboratory studies investigating airborne Burkholderia pseudomallei have used a variety of different aerosol samplers to detect and quantify concentrations of the bacteria in aerosols. However, the performance of aerosol samplers can vary in their ability to preserve the viability of collected microorganisms, depending on the resistance of the organisms to impaction, desiccation, or other stresses associated with the sampling process. Consequently, sampler selection is critical to maximizing the probability of detecting viable microorganisms in collected air samples in field studies and for accurate determination of aerosol concentrations in laboratory studies. To inform such decisions, the present study assessed the performance of four laboratory aerosol samplers, specifically the all-glass impinger (AGI), gelatin filter, midget impinger, and Mercer cascade impactor, for collecting aerosols containing B. pseudomallei generated from suspensions in two types of culture media. The results suggest that the relative performance of the sampling devices is dependent on the suspension medium utilized for aerosolization. Performance across the four samplers was similar for aerosols generated from suspensions supplemented with 4% glycerol. However, for aerosols generated from suspensions without glycerol, use of the filter sampler or an impactor resulted in significantly lower estimates of the viable aerosol concentration than those obtained with either the AGI or midget impinger. These results demonstrate that sampler selection has the potential to affect estimation of doses in inhalational animal models of melioidosis, as well as the likelihood of detection of viable B. pseudomallei in the environment, and will be useful to inform design of future laboratory and field studies.